2020
DOI: 10.1111/1365-2745.13543
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs in above‐ and below‐ground biomass allocation influencing seedling growth in a tropical forest

Abstract: 1. Plants allocate biomass to different organs in response to resource variation for maximizing performance, yet we lack a framework that adequately integrates plant responses to the simultaneous variation in above-and below-ground resources. Although traditionally, the optimal partition theory (OPT) has explained patterns of biomass allocation in response to a single limiting resource, it is well-known that in natural communities multiple resources limit growth. We study trade-offs involved in plant biomass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 65 publications
(82 reference statements)
1
24
0
Order By: Relevance
“…Our results suggest that we can gain additional insights about the role of traits predicting variation in growth not only by accounting for trait interactions but by considering the different patterns of trait variation (individual and species level) across trait types (Armbruster 1991) using hierarchical approaches (Marks 2007; Table 2). The individual‐level traits would represent the adjustability to local conditions showing high intraspecific variation (biomass allocation; Umaña et al 2020b), while the species‐level traits are likely subject to different types of constraints that makes them less variable within species than across species (i.e., SLA; Umaña et al 2018). We suggest, therefore, that traits should be modeled by recognizing differences in constraints across trait types such that biomass allocation traits display high within species variation, have a more direct effect on performance, and interact with organ‐level traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that we can gain additional insights about the role of traits predicting variation in growth not only by accounting for trait interactions but by considering the different patterns of trait variation (individual and species level) across trait types (Armbruster 1991) using hierarchical approaches (Marks 2007; Table 2). The individual‐level traits would represent the adjustability to local conditions showing high intraspecific variation (biomass allocation; Umaña et al 2020b), while the species‐level traits are likely subject to different types of constraints that makes them less variable within species than across species (i.e., SLA; Umaña et al 2018). We suggest, therefore, that traits should be modeled by recognizing differences in constraints across trait types such that biomass allocation traits display high within species variation, have a more direct effect on performance, and interact with organ‐level traits.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for aboveground strategies, light availability is one of the most important resources determining plant strategies and functional diversity (Poorter and van der Werf 1998, Poorter and Rozendaal 2008, Umaña et al 2020 a ). Further, for tropical forests, light in the understory is highly limiting and key for determining the successful recruitment and establishment of seedlings (Chazdon and Fetcher 1984, Denslow 1987, Umaña et al 2020 b ). Therefore, predictions of plant demography should consider light heterogeneity in the understory when modeling plant growth rates as a function of functional traits.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthate allocation has a very important position in the growth strategies of plants, as well as substance-recycling and energy-flow in ecosystems (Yan et al, 2016 ; Song et al, 2021 ; Umaña et al, 2021 ). However, the measurement processes for photosynthesis during the production, transfer, and consumption stages are difficult due to the complexity of the engineering and technology required (McCarthy and Enquist, 2007 ; Umaña et al, 2021 ). For instance, Bebre et al ( 2021 ) found that excessive drought can reduce the allocated biomass in the plant's aboveground parts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Song et al ( 2021 ) concluded that biomass allocation is influenced by both plant ontogeny and leaf traits. Therefore, biomass allocation at the organ level (branch, foliage, stem, and root) is often used, instead of photosynthate allocation, to gain a deeper understanding of the strategy and adaptability involved in overall survival in heterogeneous environments (Song et al, 2021 ; Umaña et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, leaves are a source organ for carbon assimilation, while stems and roots are important organs that are related to carbon storage [21]. Additionally, previous studies have demonstrated that plants can adjust the biomass ratio of photosynthetic and non-photosynthetic tissues to maintain their functional balance and resist the damage caused by environmental stress [22,23]. Growth traits and biomass are also important components of seedling quality evaluations [24,25].…”
Section: Introductionmentioning
confidence: 99%